2000
DOI: 10.1182/blood.v95.8.2569
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of PRV-1, a novel member of the uPAR receptor superfamily, which is overexpressed in polycythemia rubra vera

Abstract: Polycythemia vera (PV) is a clonal stem cell disorder characterized by hyperproliferation of the erythroid, myeloid, and megakaryocytic lineages. Although it has been shown that progenitor cells of patients with PV are hypersensitive to several growth factors, the molecular pathogenesis of this disease remains unknown. To investigate the molecular defects underlying PV, we used subtractive hybridization to isolate complementary DNAs (cDNAs) differentially expressed in patients with PV versus normal controls. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
79
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(82 citation statements)
references
References 36 publications
1
79
0
2
Order By: Relevance
“…NB1 glycoprotein is a ligand for platelet endothelial cell adhesion molecule‐1 (PECAM‐1), and participates in neutrophil transmigration (6). CD177 gene is highly homologous to a gene overexpressed in neutrophils from patients with polycythemia rubra vera called PRV‐1 (7). While studying CD177 mRNA expression in polycythemia vera (PV) patients, Zoi et al., (8) extended their study to include individuals with β‐thalassemia.…”
mentioning
confidence: 99%
“…NB1 glycoprotein is a ligand for platelet endothelial cell adhesion molecule‐1 (PECAM‐1), and participates in neutrophil transmigration (6). CD177 gene is highly homologous to a gene overexpressed in neutrophils from patients with polycythemia rubra vera called PRV‐1 (7). While studying CD177 mRNA expression in polycythemia vera (PV) patients, Zoi et al., (8) extended their study to include individuals with β‐thalassemia.…”
mentioning
confidence: 99%
“…The cloning of a novel gene named polycythaemia rubra vera‐1 (PRV‐1) which codes for a cell surface receptor was recently described by Temerinac et al . (17). They found that mRNA from the PRV‐1 gene was overexpressed in granulocytes from patients with PV, and occasionally in patients with ET and idiopathic myelofibrosis.…”
mentioning
confidence: 99%
“…Polycythemia vera is a chronic disorder of haematopoiesis that is associated with the increased production or red blood cells, platelets and neutrophils. Temerinac and colleagues compared genes expressed in neutrophils from patients with polycythemia rubra vera with genes expressed by neutrophils from healthy subjects [14]. They found that high copy numbers of mRNA from one gene were present in neutrophils from patients with polycythemia vera, but nearly absent from neutrophils from healthy subjects.…”
Section: Overexpression Of Neutrophil Cd177 Mrna and Polycythemia Veramentioning
confidence: 99%
“…They found that high copy numbers of mRNA from one gene were present in neutrophils from patients with polycythemia vera, but nearly absent from neutrophils from healthy subjects. They called this gene PRV‐1 [14]. Independently, Kissel and colleagues sequenced the gene that encodes NB1 glycoprotein and found that the NB1 gene was highly homologueous to PRV‐1 [15].…”
Section: Overexpression Of Neutrophil Cd177 Mrna and Polycythemia Veramentioning
confidence: 99%
See 1 more Smart Citation